Examining Warning Response Among Spanish Speakers in the United States to Enhance Multilingual Wireless Emergency Alerts - Trujillo-Falcón, Joseph E. (My University, 2024)
As one of the fastest growing groups in the United States, the Spanish-speaking population of 41.2 million represents one in ten Americans today. Spanish-speaking communities in the United States come from diverse backgrounds in Latin America, Europe, and Africa, each with unique cultural practices and hazard experiences tied to their places of origin. Such diversity, while enriching, poses considerable challenges for risk communicators trying to engage with multilingual populations in disaster contexts. Addressing the linguistic and cultural needs of these communities demands evidence-based research to establish best practices in our current emergency system. This dissertation has two objectives aiming to enhance emergency communication systems and messages for the U.S. Spanish-speaking public. First, by integrating intercultural communication concepts, this qualitative dissertation investigates the role of cultural factors—such as disaster subcultures, dialects, and immigration status— in the understanding of warning systems by multilingual speakers in the United States. Second, by employing two risk communication frameworks, I examine how Spanish speakers in the United States respond to existing mobile, multilingual emergency warnings known as Wireless Emergency Alerts (WEAs). More specifically, I employ the warning response model (WRM) and the extended parallel process model (EPPM) to examine both the cognitive processes of warning reception and the emotional behaviors involved in decision making. To achieve these goals, I conducted 27 think-aloud and semi-structured interviews with members of the Spanish-speaking population. Through subsequent constant comparative analysis, my results from the two objectives unravel how language disparities and cultural disconnect exacerbate vulnerabilities for non-English speaking populations. First, I found that Spanish speakers in the United States interpret their local warning systems through multiple perspectives. Foreign-born immigrants experienced culture shock upon encountering U.S. warning systems for the first time and reported similar adaptation processes overall. U.S.-born Spanish speakers understood warning systems not only through their local geography but also through cultural experiences derived from their community and ethnic origins in Latin America. Spanish speakers living in border communities experienced differing and sometimes conflicting warning systems between the United States and Mexico. Undocumented immigrants resisted adapting to U.S. warning systems, recognizing the systemic injustices underlying these emergency systems. Second, I discovered that clear, consistent, culturally competent, and jargon-free messages empower Spanish speakers to take protective action against natural hazards like tornadoes. These effective messages were almost always the 360-character WEA messages, as they provided the necessary contextual information. I use these insights to provide recommendations for a more inclusive multilingual emergency system in the United States. I advocate for increased coordination between governmental agencies, community leaders, and international entities, fostering a learning environment to better tailor messages for multilingual groups. Additionally, I propose the implementation of WEAs in multilingual settings to reach more underserved communities. Based on insights from my participants, I propose slight modifications to 360-character Spanish-language WEAs, which were overwhelmingly favored by my respondents. Through these recommendations, I outline a vision for a future multilingual emergency system, highlighting the key cultural and linguistic factors that need to be considered to ensure warning equity for all.
Keywords: risk communication; bilingualism; wireless emergency alerts; hispanic/latino